ʻUlamāʼe-Maẓāhir-i ʻUlūm, Sahāranpūr, aur unkī ʻilmī va taṣnīfī ḵẖidmāt - Shāhid Sahāranpūrī, Sayyid Muḥammad (Kutub Ḵẖānah Ishāʻat al-ʻUlūm, 1982)
On Maẓāhir-i ʻUlūm, Saharanpur, center for Arabic language and Islamic studies, and lives and works of its alumni.